Late Quaternary (≥MIS 3 to MIS 1) stratigraphic transitions in a highland Beringian landscape along the Kuskokwim River, Alaska. Issue 1 (January 2020) - Reuther, Joshua D.; Rogers, Jason; Druckenmiller, Patrick; Bundtzen, Thomas K.; Wallace, Kristi; Bowman, Robert; May, Kevin; Feathers, James; Cherkinsky, Alexander
Abstract: Stratigraphic records extending to Marine Oxygen Isotope Stage (MIS) 3 (57, 000–29, 000 cal yr BP) or older in Beringia are extremely rare. Three stratigraphic sections in interior western Alaska show near continuous sedimentological and environmental progressions extending from at least MIS 3, if not older, through MIS 1 (14, 000 cal yr BP–present). The Kolmakof, Sue Creek, and VABM (vertical angle bench mark) Kuskokwim sections along the central Kuskokwim River, once a highland landscape at the fringe of central and eastern Beringia, contain aeolian deposition and soil sequences dating beyond 50, 000 14 C yr BP. Thick peaty soil, shallow lacustrine, and tephra deposits represent the MIS 3 interstade (or older). Sand sheet and loess deposits, wedge cast development, and very thin soil development mark the later MIS 3 period and the transition into the MIS 2 stade (29, 000–14, 000 cal yr BP). Loess accumulation with thicker soil development occurred between ~16, 000–13, 500 cal yr BP at the MIS 2 and MIS 1 transition. After ~13, 500 cal yr BP, loess accumulation waned and peat development increased throughout MIS 1. These stratigraphic sequences represent transitions between a warm and moist period during MIS 3, to a cooler and more arid period during MIS 2, then a return to warmer and moister climates in MIS 1.